2008
DOI: 10.1016/j.pbb.2008.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Systemic administration of the adenosine A2A agonist CGS 21680 induces sedation at doses that suppress lever pressing and food intake

Abstract: Adenosine A 2A receptors are involved in the regulation of several behavioral functions. Adenosine A 2A antagonists exert antiparkinsonian effects in animal models, and adenosine A 2A agonists suppress locomotion and impair various aspects of motor control. The present experiments were conducted to study the effects of low doses of the adenosine A 2A agonist CGS 21680 on lever pressing, specific parameters of food intake, and sedation. In the first experiment, the effects of CGS 21680 on fixed ratio 5 lever pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
26
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 64 publications
3
26
0
Order By: Relevance
“…Inhibitory effects of CGS 21680 on both FR and PR schedules of cocaine self-administration clearly indicate an action on motivational properties of cocaine which is in line with other behavioral reports in rats showing an effective reduction of cocaine addictive responses following A 2A receptor agonism or in rats overexpressing neuronal A 2A receptors (for review see Filip et al 2012). Similarly in a food self-administration paradigm, CGS 21680 dose dependently blocked operant responding for food, and this finding extends previous studies in which the A 2A receptor agonist, following systemic or accumbal injections, reduced effort-related food choice behavior (Font et al 2008;Mingote et al 2008) or bingerelated eating disorders (Micioni di Bonaventura et al 2012).…”
Section: Discussionsupporting
confidence: 84%
“…Inhibitory effects of CGS 21680 on both FR and PR schedules of cocaine self-administration clearly indicate an action on motivational properties of cocaine which is in line with other behavioral reports in rats showing an effective reduction of cocaine addictive responses following A 2A receptor agonism or in rats overexpressing neuronal A 2A receptors (for review see Filip et al 2012). Similarly in a food self-administration paradigm, CGS 21680 dose dependently blocked operant responding for food, and this finding extends previous studies in which the A 2A receptor agonist, following systemic or accumbal injections, reduced effort-related food choice behavior (Font et al 2008;Mingote et al 2008) or bingerelated eating disorders (Micioni di Bonaventura et al 2012).…”
Section: Discussionsupporting
confidence: 84%
“…This study employed a sedation rating scale adapted from Salamone et al (1996) and Chuck et al (2006), and showed that, in the same systemic dose range that also suppressed FR5 lever pressing and feeding, CGS 21680 (0.05 and 0.1 mg/kg IP) significantly induced overt signs of sedation/drowsiness that included foot dragging, stumbling, ataxia, flattened posture, lowered head, and partially closed eyes. In the Mingote et al (2008) study, 0.1 mg/kg CGS 21680 produced a level of sedation that was comparable to that induced by 2.0 g/kg ethanol (Chuck et al 2006), which is a dose of ethanol that also suppressed lever pressing. Thus, the absence of a shift from lever pressing to chow intake following systemic administration of CGS 21680 is likely to be due to a sedation/ drowsiness effect.…”
Section: Discussionmentioning
confidence: 83%
“…Also, drugs that produce substantial drowsiness/sedation (e.g. the adenosine A 2A agonist CGS 21680) have been shown to decrease both lever pressing and chow intake (Mingote et al 2008b), and did not induce the shift from lever pressing to chow intake at systemic doses that induced sedation (Font et al 2008). Our own pilot studies indicated that higher doses of IL-1β could suppress food intake in addition to lever pressing, but the low doses used in experiments 1 above enabled us to observe a shift if choice from lever pressing to chow intake.…”
Section: Discussionmentioning
confidence: 99%